2004
DOI: 10.1182/blood-2004-02-0693
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of human fetal mesencyhmal stem cells to Kaposi sarcoma-associated herpesvirus

Abstract: IntroductionThe etiologic agent of Kaposi sarcoma (KS), KS-associated herpesvirus (KSHV), 1 infects a number of cell types within KS lesions, including endothelial cells, monocyte-derived cells, and characteristic "spindle cells" that help define these tumors. 2,3 Within infected individuals, a variety of circulating bone marrowderived cells also can harbor KSHV DNA. Some of these cells can transform to spindle-shaped cells displaying morphology and cell surface characteristics similar to KS spindle cells. [4]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 23 publications
3
41
0
Order By: Relevance
“…We observed a profound dose-dependent inhibitory effect of IFNg on toxoplasma growth, which was completely reversed by addition of supplementary tryp (Figure 1c) confirming that IDO-mediated tryp depletion indeed contributes to MSC-mediated antiparasitic effector function. As recent reports have demonstrated that MSCs might be target of infections with human herpesviruses representing prominent pathogens in the setting of allogeneic hematopoietic stem cell transplantation, 8,16 we next investigated the potential impact of IDO-expression on replication of human CMV in MSCs. With increasing amounts of IFNg, we detected a 42.5-log decrease in CMV replication in MSC monolayer cultures as determined by quantitative PCR for CMV genome copy number after a 3-day culture period (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
“…We observed a profound dose-dependent inhibitory effect of IFNg on toxoplasma growth, which was completely reversed by addition of supplementary tryp (Figure 1c) confirming that IDO-mediated tryp depletion indeed contributes to MSC-mediated antiparasitic effector function. As recent reports have demonstrated that MSCs might be target of infections with human herpesviruses representing prominent pathogens in the setting of allogeneic hematopoietic stem cell transplantation, 8,16 we next investigated the potential impact of IDO-expression on replication of human CMV in MSCs. With increasing amounts of IFNg, we detected a 42.5-log decrease in CMV replication in MSC monolayer cultures as determined by quantitative PCR for CMV genome copy number after a 3-day culture period (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, MSC in general are not susceptible to EBV. Parsons et al 42 recently described that fetal MSC are susceptible to human herpesvirus 8/Kaposi's sarcomaassociated herpesvirus (HHV8/KSHV) belonging to the same subfamily of gammaherpesvirus as EBV. Mesenchymal stem cells are infected by both cell-free and cell-bound HHV8/KSHV, but supernatants could not transmit infection to naı¨ve cells.…”
Section: Discussionmentioning
confidence: 99%
“…86 Yet attention must be paid to the direct susceptibility of BMSCs to infectious pathogens. Fetal BMSCs have been shown to be in vitro targets for Kaposi sarcoma virus, 87 which may explain hematopoietic deficiencies and BM failures in these patients given the role of MSCs in hematopoiesis as previously reviewed. BMSCs have also been shown to harbor and transmit parvovirus B19 to hematopoietic cells in vitro.…”
Section: Bmsc Effects On Hscsmentioning
confidence: 99%